Gender-Dependent Crossmodal Interactions Between Olfactory and Tactile Stimulation Revealed Using the Unimodal Tactile Stimulation Device (UniTaSD) - Sijben, Rik; Hensel, Sonja M.; Rodriguez-Raecke, Rea; Freiherr, Jessica (Chemical Senses, 2021)
Due to the complex stimulation methods required, olfaction and touch are 2 relatively understudied senses in the field of perceptual (neuro-)science. In order to establish a consistent presentation method for the bimodal stimulation of these senses, we combined an olfactometer with the newly developed Unimodal Tactile Stimulation Device. This setup allowed us to study the influence of olfaction on tactile perception and opened up an unexplored field of research by examining the crossmodal influence of tactile stimuli on olfaction. Using a pseudorandomized design, we analyzed how positive or negative tactile and olfactory stimuli influenced the opposing modality's perceived intensity and pleasantness. By asking participants to rate tactile stimuli, we were able to reproduce previously reported differences indicating that bimodal presentation with an olfactory stimulus increases or reduces perceived tactile pleasantness in an odor-dependent manner while highlighting that this effect appears unique to women. Furthermore, we found the first evidence for the influence of tactile stimuli on perceived odor pleasantness, an effect that is also driven primarily by women in our study. Based on these findings we believe that future neurophysiological studies, using controlled stimulus presentation can help unravel how and why olfactory and tactile perception interact in the human brain.
CRIS-Team Scopus Importer:2021-04-19
Keywords: crossmodal interaction; olfaction; perception; tactile; touch